The Frequency of Mobile Banking Use During COVID-19 - Pokhrel, Laxman (NRB Economic Review, 2022)
The purpose of this paper is to examine the frequency of mobile banking use during COVID-19. Data were collected from 226 respondents. Data have been analyzed by applying the two-stage structural modeling technique through Partial Least Squares-Structural Equation Modeling (PLS-SEM). This study has found a significant positive impact of attitude towards mobile banking, subjective norms, and perceived behavior control on behavior intention mobile banking adoption. However, the risk perception of COVID-19 has no effect on the intention of mobile banking adoption. Based on the findings of this research, some theoretical and practical implications have been provided.